TEACHER’S ATTITUDES TOWARD THE USE OF ENGLISH TEXTBOOK: A CASE STUDY FOR ENGLISH TEACHERS AT SMP N 4 AMBON - Solissa, Herry Robinson; Que, Stella Rose; M, Monica (Pattimura Excellence Journal of Language and Culture, 2023)
The textbook plays an important role in the teaching and learning process. However, in reality, weaknesses in textbooks often manifest. The purpose of this study was to understand the attitudes exhibited by teachers towards these weaknesses in textbooks. Additionally, this research aimed to examine whether teachers chose to display their attitudes by either using the textbooks as they were or revising them. This study employs a qualitative research approach utilizing a case study method and employs various instruments to collect data: observation checklists, interviews, questionnaires, and documentation. The study involves three teachers from SMP N 4 Ambon as its subjects. The findings revealed a positive attitude among teachers regarding textbook usage. This positivity stems from teachers incorporating materials and exercises from other sources while still utilizing textbooks and engaging in reflective practices. The teachers expressed satisfaction with this positive attitude as it enhanced teaching and learning activities.